Comparison of Effectiveness of Prolotherapy and Corrective Exercise Program vs Prolotherapy and Isometrics Strengthening on Pain and Functional Improvement in Supraspinatus Tendinopathy in a Tertiary Care Centre - Sai Kishore; Praveen Ravi; Dobson Dominic; Ramya Gnanapragasam (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2023)
Background Regenerative injection therapies such as prolotherapy have gained importance in the recent years in non-surgical management of supraspinatus tendinopathy. The aim of the present study was to compare the efficacy of isometric rotator cuff strengthening versus corrective exercise program in the treatment of supraspinatus tendinopathy. Material and Methods Fifty patients aged 18 - 60 years were recruited with MRI diagnosed isolated supraspinatus tendinopathy or < 50% thickness tear and symptoms persisting for longer than 6 months. All patients were randomised into two groups: one prolotherapy with isometric rotator cuff strengthening exercise therapy (group ISE; n = 25) and the other group also treated with prolotherapy injection followed by corrective exercise program (group CEP; n = 25). Patients were examined at baseline, 3, 6, and 12 weeks. Improvement was assessed using a visual analog scale (VAS) for pain, and Constant Murley Score (CMS) for shoulder function. Results Significant difference (p < 0.001) was found between the groups in the VAS and CMS at any follow-up period. Conclusion Prolotherapy with CEP is more beneficial than prolotherapy with isometric strengthening exercise in supraspinatus tendinopathy. Improvement in pain and functional movements is more in the prolotherapy with CEP group than prolotherapy with ISE group.